En Bloc Transplantation of Horseshoe Kidney from Deceased Donor: An Unusual Transplantation Utilizing Kidneys with Congenital Fusion Abnormality - Bodhisatwa Sengupta; Iftikhar Khan; Akram Saiaghi; Ethar A. Gaw; Mansour Tawfeeq; Mohammed S. AlQahtani; Mahmoud Obeid (Case Reports in Transplantation)
Transplanting horseshoe kidneys is challenging and has higher complication rates due to the unusual anatomy of the vascular and urinary collecting systems. Most centers avoid using these kidneys for transplantation. However, if chosen carefully, these organs can be used successfully to reduce organ shortage. In this paper, we will describe the technique of procurement of horseshoe kidneys from cadaveric donors, back table preparation, and its successful implantation in a recipient. With good planning and skillful surgical techniques, horseshoe kidneys can be successfully transplanted in suitable recipients. If properly selected, these kidneys can be used to reduce the organ scarcity and diminish waitlist morbidity and mortality.